2020
DOI: 10.3390/cancers12113450
|View full text |Cite
|
Sign up to set email alerts
|

Is the Proteome of Bronchoalveolar Lavage Extracellular Vesicles a Marker of Advanced Lung Cancer?

Abstract: Acellular bronchoalveolar lavage (BAL) proteomics can partially separate lung cancer from non-lung cancer patients based on principal component analysis and multivariate analysis. Furthermore, the variance in the proteomics data sets is correlated mainly with lung cancer status and, to a lesser extent, smoking status and gender. Despite these advances BAL small and large extracellular vehicles (EVs) proteomes reveal aberrant protein expression in paracrine signaling mechanisms in cancer initiation and progress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
20
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 57 publications
7
20
1
Order By: Relevance
“…This result indicated that CLEC3B, ITIH4, SERFINF1, SAA4, SERFINC1, and C20ORF3 cannot serve as effective biomarkers for lung cancer. CD5L was also detected in the EVs from bronchoalveolar lavage of lung cancer patients, but there was no correlation to the tumor progress [ 28 ]. It is attributed to the different sample numbers ( n = 24 for bronchoalveolar lavage) to our study ( n = 80), the different isolation methods used in the two studies (ultracentrifugation vs. magnetic separation), and the difference in the sample origin.…”
Section: Discussionmentioning
confidence: 99%
“…This result indicated that CLEC3B, ITIH4, SERFINF1, SAA4, SERFINC1, and C20ORF3 cannot serve as effective biomarkers for lung cancer. CD5L was also detected in the EVs from bronchoalveolar lavage of lung cancer patients, but there was no correlation to the tumor progress [ 28 ]. It is attributed to the different sample numbers ( n = 24 for bronchoalveolar lavage) to our study ( n = 80), the different isolation methods used in the two studies (ultracentrifugation vs. magnetic separation), and the difference in the sample origin.…”
Section: Discussionmentioning
confidence: 99%
“…Both pathways were described as involved in cancer promotion [ 99 , 100 ]. Researchers selected also the protein DNA (cytosine-5)-methyltransferase 3β (DNMT3B) complex as significantly upregulated in BALF-EVs from lung cancer patients [ 101 ]. The DNMT3B complex is responsible for de novo epigenetic modifications and considered as a prospective therapeutic target [ 102 ].…”
Section: Balf-evs As Biomarkersmentioning
confidence: 99%
“…The possibility to diagnose and screen DLBCL patients for treatment based on liquid biopsies by targeting the proteome of extracellular vesicles (EVs) is unexplored and provides clear advantages. Minimally invasive liquid biopsy-based diagnosis and patient screen opens new avenues for fast and longitudinal follow up for minimal residual disease assessment [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…EVs have attracted much recent interest because of their potential functions, use as disease biomarkers, and possible therapeutic exploitation [12,13]. EVs are extracellular vesicles of endosomal and plasma membrane origin released in vivo into the extracellular environment by cells as distinct as B lymphocytes and dendritic cells as well as from several additional cell types of hematopoietic origin [14].…”
Section: Introductionmentioning
confidence: 99%